2001
DOI: 10.2169/internalmedicine.40.336
|View full text |Cite
|
Sign up to set email alerts
|

Compound Heterozygosity for Alpha-1-antitrypsin (Siiyama and QOclayton) in an Oriental Patient.

Abstract: Alpha-1-antitrypsin (alAT) deficiency is extremely rare among Orientals. Wetreated a 37-year-old man with severe pulmonary emphysema associated with a low serum concentration of alAT. Mutation analysis of the alA T gene was performed using a reverse transcription-polymerase chain reaction followed by sequencing. The patient proved to be a compoundheterozygote carrying a Siiyama deficient allele and a QOclayton null allele. This is the first Japanese case of alAT deficiency to arise from such compoundheterozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Of the 14 cases in which the genetic defects have been elucidated, 10 are unrelated cases of Siiyama (13), one case contained the Mnichinan allele (14,15), one was a Mmaltonheterozygote case (16), an additional compoundheterozygote carried a Siiyama allele and a QOclayton null allele (17), and the last case was associated with 14q-syndrome (18). It was later found that our patient was a sister of the proband (II-7 in Fig.…”
Section: Case Reportmentioning
confidence: 77%
“…Of the 14 cases in which the genetic defects have been elucidated, 10 are unrelated cases of Siiyama (13), one case contained the Mnichinan allele (14,15), one was a Mmaltonheterozygote case (16), an additional compoundheterozygote carried a Siiyama allele and a QOclayton null allele (17), and the last case was associated with 14q-syndrome (18). It was later found that our patient was a sister of the proband (II-7 in Fig.…”
Section: Case Reportmentioning
confidence: 77%
“…It has only been reported in a U.S. Caucasian family, a Korean family, and a Japanese family. 6,7 A total of 11 cases of S/Null genotype were found. Of S/Null genotypes two were heterozygotes of Q0 Clayton and S iiyamma which is a specific S variant with more severe disease than other S variants.…”
Section: Discussionmentioning
confidence: 99%
“…We described the protein variations in a codon numbered from the methionine residue at the translation initiation site. However, the first 24 amino acids of AAT act as a signal peptide [ 9 , 10 ], and therefore, many studies numbered the codon from the glutamic acid at the 25th position [ 5 , 7 , 11 ]. There is no consensus about this issue and many articles and/or databases designate the same variations with different numbers [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%